THE EFFECT OF RELIGIOSITY, KNOWLEDGE, AND SERVICE QUALITY TO PEOPLE’S INTEREST IN IMPLEMENTING CASH WAQF - Farid Setyawan, Arditya (Dinasti Publisher, 2021)
This research has the purpose to reveal the impact which is caused by religiosity, knowledge and service quality on people's interest in implementing cash waqf. The method used in this research through a survey method. The research population was all the people who had done cash waqf with a total sample of 60 people. The research data used was primary data that gathered through distributing questionnaires to samples or research respondents. The analytical tool used was linear regression, correlation, coefficient of determination and hypothesis test. The results showed that: (1) The regression coefficient of religiosity on interest was -0.062, so the religiosity did not have a positive impact on employee performance. (2) The regression coefficient value of knowledge on interest was 0.265, so the knowledge had a positive impact on interest. (3) The value from service quality regression coefficient on interest was 0.292, so the service quality had a positive impact on interest. (4) The results showed that religiosity, knowledge and services quality simultaneously had an affects on the interest variable.